TMOD-30. CHARACTERIZATION OF AN ALTERNATIVELY SPLICED NTRK2 VARIANT IN GLIOMAS - Pattwell, Siobhan (Neuro Oncol, 2019)
Recent work has uncovered oncogenic TRK fusions in a wide range of cancer types, including adult and pediatric gliomas. With some exceptions, many of these fusions tend to occur at very low frequencies below 1–2%, with unclear clinical significance, yet they highlight a potentially important and rapidly evolving role for NTRK1, NTRK2, NTRK3 in glioma biology. Basic scientific and clinical investigation surrounding TRKs’ role in cancer has often been hindered due to the nonspecific nature of antibodies and kinase inhibitors, combined with a lack of precise exon-specific expression data from patient populations. Tropomyosin receptor B (TrkB), encoded by the NTRK2 gene, is most known for its established roles in neuronal survival, proliferation, differentiation, apoptosis, learning, and memory. TrkB exerts diverse effects on cellular outcomes through interactions with downstream signaling cascades and has been shown to exhibit complex alternative splicing patterns. Here we show a novel role for a TrkB splice variant in human gliomas via NTRK2 transcript analyses in normal human brain and gliomas using The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression Project (GTEx). Using a novel antibody designed against this splice variant, immunostaining shows altered receptor localization within human gliomas compared to normal human brain. This NTRK2 splice variant enhances PDGF-driven gliomas in vivo in an RCAS-TVA mouse model and augments PDGF-induced signaling in vitro. Through the lens of NTRK2, these results highlight the importance of expanding upon whole gene-level and kinase-fusion analyses to explore TRK splicing in basic and translational research.